Eurytrematosis: a Review of the Pancreatic Fluke - Ummu Balqis (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
Eurytrematosis is a common zoonotic disease has emerged as a major species causing veterinary diseaseand public health problem. This review examines recent advances in Eurytrema species, the life cycle, intermediatehosts required for completing the life cycle, and geographical distribution of Eurytrema species in the world, as wellas several factors considered suitable to occur.